2002
DOI: 10.1046/j.1432-1327.2002.02843.x
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in the ATP synthase of Rhodobacter capsulatus results in differential contributions of DeltapH and Deltaphi in driving the ATP synthesis reaction

Abstract: The interface between the c-subunit oligomer and the a subunit in the F 0 sector of the ATP synthase is believed to form the core of the rotating motor powered by the protonic flow. Besides the essential cAsp61 and aArg210 residues (Escherichia coli numbering), a few other residues at this interface, although nonessential, show a high degree of conservation, among these aGlu219. The homologous residue aGlu210 in the ATP synthase of the photosynthetic bacterium Rhodobacter capsulatus has been substituted by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In a study using F o F 1 from chloroplasts, ATP was synthesized after an acidbase transition in the absence of ⌬⌿ (28). There were several lines of evidence indicating that both ⌬pH and ⌬⌿ are capable of driving the ATP synthesis reaction (14,(27)(28)(29). However, Kaim and Dimroth (15) have reported that the ATP synthesis reaction by E. coli F o F 1 depends on ⌬⌿ and could not be energized by ⌬pH only (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using F o F 1 from chloroplasts, ATP was synthesized after an acidbase transition in the absence of ⌬⌿ (28). There were several lines of evidence indicating that both ⌬pH and ⌬⌿ are capable of driving the ATP synthesis reaction (14,(27)(28)(29). However, Kaim and Dimroth (15) have reported that the ATP synthesis reaction by E. coli F o F 1 depends on ⌬⌿ and could not be energized by ⌬pH only (15).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive mutagenesis studies revealed that residues Arg-210, His-245 and Glu-219 of subunit a (E. coli numbering) are involved in ion transport [43][44][45], but recent studies revealed that only Arg-210 is essential for ion conduction [46]. This residue is in close proximity to the active carboxylate of subunit c (Asp-61 in E. coli) [44,46,47], and as we shall see later, both residues are key players in ion transport.…”
Section: Structure and Function Of The F O Domainmentioning
confidence: 99%
“…capsulatus B100 are available (Borghese et al 1998a, b) and genetic techniques for site-specific mutagenesis have been set up (Turina and Melandri, 2002). These studies have lead to the production of a number of site-specific mutants and, for some of these, to the functional characterization of their phenotypes (Turina and Melandri 2002). [For a historical perspective on ATP Synthase, see W Junge (pp 571-595) in Govindjee et al (2005).…”
mentioning
confidence: 99%